2011
DOI: 10.1007/s10453-011-9208-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonal dynamics of airborne bacteria in the Mogao Grottoes, Dunhuang, China

Abstract: The aim of this study was to analyze the phylogenetic composition of the bacterial community in the air at the Mogao Grottoes (Dunhuang, China) using a culture-dependent molecular approach. The 16S rRNA genes were amplified directly from the isolates with universally conserved and bacteria-specific rRNA gene primers. The PCR products were screened by restriction fragment length polymorphism, and representative rRNA gene sequences were determined and sequenced. A total of 19 bacteria genera were identified amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
17
0
2
Order By: Relevance
“…The influence of tourists and environmental factors were identified as the main factors contributing to biodeterioration 16 17 . In addition, microbial species with the potential to damage paintings or act as opportunistic pathogens to visitors were identified 18 19 .…”
mentioning
confidence: 99%
“…The influence of tourists and environmental factors were identified as the main factors contributing to biodeterioration 16 17 . In addition, microbial species with the potential to damage paintings or act as opportunistic pathogens to visitors were identified 18 19 .…”
mentioning
confidence: 99%
“…These buildings offer unique chemical environments, not encountered in the natural world, that may enhance the development of bioaerosols [11]. Bioaerosols are a large category of airborne particles, comprising bacteria, fungi, viruses, pollen, and fragments of these or their metabolic products (e.g., mycotoxins), and endotoxins (part of the outer membrane of the cell wall of Gram-negative bacteria), and they can contribute to around 5-34% of indoor air pollution [12][13][14]. Bioaerosols can become a serious risk to the health of the population, airborne bacteria and fungi, in particular, can cause infectious diseases, allergic and toxic effects [11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using a similar sampling approach, Wang et al (2012) found that some of the dominant genera inside cave air included Micrococcus , Sphingomonas , Pseudomonas , and Bacillus ; which were also dominant in our aerosol samples. Urbano et al (2011) found a dominance of Bacillus in marine aerosol sampled in California.…”
Section: Discussionmentioning
confidence: 78%